Analysis of Microwave Communication Network Planning on Ocean Topography Using Space Diversity - Arrizky Ayu Faradila Purnama; Muhammad Imam Nashiruddin (Centre for Research and Development on Resources, Equipment, and Operations of Posts and I, 2020)
One of the challenges often met by planners of the telecommunications network using microwave radio is surface conditions, especially when passing through the ocean. Propagation conditions above sea surface often result in increasing fading, which significantly affects the reliability of the microwave network. On the other hand, considering that Indonesia is an archipelago, ocean topography is unavoidable, and the use of microwave networks generally considered to be the most efficient among other technologies, especially in Eastern Indonesia. This research aims to respond to such a challenge by planning a microwave communication network using a space diversity technique. The type of microwave network used is a point to point, which links Bali and Lombok islands. The results showed that the use of space diversity techniques could increase fading margins from 34.42 dB to 35.15 dB and availability value from 99.99667% to 99.99873%. Therefore, this technique recommends implementing by telecommunications network providers in accelerating the deployment of connecting networks in areas that have ocean topography.